Meningkatkan Repurchase Intention Melalui Peran Mediasi Perceived Value: Studi Kasus di Miss Unicorn Cafe Bekasi - Rosmawati; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to analyze the effect of service quality and atmosphere on repurchase intentions through perceived value. The population of this study was buyers who had visited Miss Unicorn Cafe Bekasi, using primary data obtained from 150 respondents at Miss Unicorn Cafe. The method used to analyze the data in this study is PLS-SEM. Meanwhile, hypothesis testing includes path analysis, evaluation of measurement models and structural models, direct influences, and indirect influences. The author uses a quantitative descriptive method, namely by analyzing data using SmartPLS 3.0. The results showed that overall the quality of service and atmosphere had a significant effect on repurchase intention through perceived value. The role of mediation that is considered valuable has played a strong influence and therefore this model is highly recommended to be maintained by management of Miss Unicorn Cafe. Keywords : Service Quality, Atmosphere, Perceived Value, Repurchase Intention